Improvement of qualification of civil servants on the basis of the project approach - Yehorchenkova, Nataliia; Klievanna, Ganna Oleksiivna (КНУБА, 2021)
For employees of public authorities and local governments, the main source of new knowledge is training. It is through the in-service training system that civil servants have the opportunity to achieve a new level of professionalism and culture, to formulate the ability to competently and responsibly perform managerial functions, to gain skills in implementing the latest socially oriented technologies and innovation processes. Today, the system of professional development is seen as an effective mechanism for providing educational services and implementing public personnel policy, improving the efficiency of the civil service as a whole.
Keywords: improvement of qualification of civil servants; project approach; 331.363:35-051